Analisis Penetapan Margin Akad Murabahah Pada Bank Syariah di Indonesia - Eka Nuraini Rachmawati; Azmansyah Azmansyah; Raja Ria (Jurnal Ekonomi KIAT, 2017)
The purpose of this research is to know the way or model by syariah banking in determining margin level of murabahah financing contract. The sample of this research consist of 1 Sharia Business Unit (UUS), and 2 Sharia Commercial Bank (BUS), namely Bank Riaukepri Syariah, Bank Muamalat, Bank Syariah Mandiri. The results of this study indicate the determination of margin on financing with murabahah scheme at Sharia Bank based on ALCO team decision of each bank refers to BI-Rate, amount of cost of fund component, overhead cost, bad credit risk, which are desired.